A Comparative Study of Metakaolin and Silica Fume on the Properties and Microstructure of Ultrafine Dredged Sand Mortars - Changpei Qin; Junxian Zhao; Yixuan Wang; Yongqi Zou; Fares Ali Al Sairafia; Chaohua Jiang (Advances in Materials Science and Engineering)
The main objective of this study is to improve the performance of ultrafine dredged sand mortars by using metakaolin (MK) and silica fume (SF) mixed with high-content FA. The mechanical properties and microstructure of the ultrafine dredged sand mortars were analyzed. The results show that the strong growth rate of the mortars with 5%, 10%, and 15% MK and SF contents, respectively, exceeds 30% at the age of 7 d. Compared with an ordinary Portland cement dredged mortar, the shrinkage of the specimens with 5% and 15% MK increases prior to 7 d and decreases by 16.9% and 13.8%, respectively, at 90 d. The addition of MK shows a better enhancement effect than that of SF, with the splitting tensile strength increased by 41.4% to 2.15 MPa with 15% MK compared with the mortar with a 50% FA content at 3 d. MK shows a higher enhancement effect than SF due to its uniquely active Al2O3. Moreover, a microstructural investigation based on scanning electron microscopy (SEM) and mercury intrusion porosimetry (MIP) confirms that the physical filling and pozzolanic effects of MK and SF can optimize the microstructure of the slurry, improve the interfacial combination of different phases, and refine the pore size distribution of cement paste. The test results prove that high-content FA ternary cementitious systems containing MK or SF represent a sustainable solution to the resource utilization of building materials based on ultrafine dredged sand.